2022
DOI: 10.1002/btm2.10431
|View full text |Cite
|
Sign up to set email alerts
|

The combination of resveratrol and Bletilla striata polysaccharide decreases inflammatory markers of early osteoarthritis knee and the preliminary results on LPS‐induced OA rats

Abstract: Osteoarthritis (OA) of the knee is characterized by progressive deterioration and loss of articular cartilage with associatedstructural and performance changes in the entire joint, and current treatments for OA only aim to relieve symptoms, rather than to prevent or reverse disease progression. Recently, treatments targeting “early osteoarthritis” (EOA) have attracted attention. However, during EOA stage, chondrocytes may change behaviors to express pro‐inflammatory cytokines and free radicals, which would cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…After birth, mice that lacked miRNA-140 exhibited deformities in bone growth and experienced apoptosis in chondrocytes. miRNA-140 holds significant prominence in the context of chondrocyte growth and development [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…After birth, mice that lacked miRNA-140 exhibited deformities in bone growth and experienced apoptosis in chondrocytes. miRNA-140 holds significant prominence in the context of chondrocyte growth and development [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chen et al determined that BSP improved the climbing ability and survival rate of adult flies by decreasing the production of reactive oxygen species, increasing antioxidant enzyme activity, and inhibiting cell death. In 2023, Lin et al confirmed that BSP combined with resveratrol effectively reduced inflammatory markers in early osteoarthritis (OA) in vitro and in preliminary lipopolysaccharide (LPS)-induced OA rat experiments. BSP is a water-soluble polysaccharide that can be directly added to the culture medium at specific concentrations for in vitro cell experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a serious chronic degenerative disease characterized by articular cartilage loss, synovitis, subchondral bone sclerosis, and osteophyte, which is the main cause of joint pain and disability 1–6 . The progression of OA may ultimately lead to keen arthroplasty surgery to restore joint function 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a serious chronic degenerative disease characterized by articular cartilage loss, synovitis, subchondral bone sclerosis, and osteophyte, which is the main cause of joint pain and disability. 1 , 2 , 3 , 4 , 5 , 6 The progression of OA may ultimately lead to keen arthroplasty surgery to restore joint function. 7 , 8 Although there are no effective disease‐modifying therapies available to delay or prevent knee replacement, intra‐articular therapies such as corticosteroids (CS), nonsteroidal anti‐inflammatory drugs (NSAIDs), and hyaluronic acid (HA) have been commonly used in clinical trials to mitigate cartilage destruction and knee pain.…”
Section: Introductionmentioning
confidence: 99%